Teaching Collocations to Non-Arabic Speakers: Challenges and Implications - Ghalyoun, Safa Mohammad Abu; Sapar, Ahmad Arifin; Seman, Haji Mohammad Bin (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2024)
This study delves into the realm of collocations within Arabic language instruction for non-native speakers, focusing on the associated challenges, difficulties in comprehension, and the influence of their rhetorical and metaphorical intricacies on learners' lexical development. It also advocates for the integration of collocations into linguistic lessons. This research is crucial due to the scarcity of comprehensive studies addressing this subject, aiming to fill the existing gap by scrutinizing a problem often overlooked in its entirety. Given its profound impact on the attainment and linguistic competence of non-Arabic speakers, collocations represent one of the most formidable hurdles in Arabic language acquisition. Their complexity, encompassing rhetorical, semantic, and cultural nuances, renders direct translation and analysis challenging.